Money, marriage, and madness : the life of Anna Ott - Nielsen, Kim E. (Urbana : University of Illinois Press, 2020)
"Anna Ott died in the Wisconsin State Hospital for the Insane in 1893. She had enjoyed status and financial success first as a physician's wife and then as the only female doctor in Madison. Throughout her first marriage, attempts to divorce her abusive second husband, and twenty years of institutionalization, Ott determinedly shaped her own life. Kim E. Nielsen explores a life at once irregular and unexceptional, revealing a woman whose whiteness and privileged place in society still failed to protect her. Historical and institutional structures, like laws that liberalized divorce and women's ability to control their property, opened up uncommon possibilities for Ott. Other structures, from domestic violence in the home to rampant sexism and ableism outside of it, remained a part of even affluent women's lives. Money, Marriage, and Madness tells a forgotten story of how the legal and medical cultures of the time shaped one woman-and what her life tells us about power and society in nineteenth century America"--
Mrs. Anna Miesse, Local Doctor's Wife -- The Questions of 1855 -- Miesse v. Miesse, -- The Questions of 1856 -- Dr. Anna B. Ott, Local Doctress -- Anna Ott, Insane Asylum Inmate -- Anna Ott, Economic Agent -- Remembering Anna Ott.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on July 16, 2020).
JSTOR
Keywords: Ott, Anna Miesse, -- 1819-1893.; Ott, Anna Miesse, -- 1819-1893.; Ott, Anna Miesse, -- 1819-1893.; Physicians' spouses -- United States -- Biography; Women physicians -- United States -- Biography; Abused wives -- United States -- Biography; Divorce -- United States -- History -- 19th century; Mentally ill -- Commitment and detention -- United States; Women -- United States -- Social conditions -- 19th century; Women physicians; Mentally ill women; Physicians, Women; Battered Women; Persons with Psychiatric Disorders; United States; Médecins -- Conjoints -- États-Unis -- Biographies; Femmes médecins -- États-Unis -- Biographies; Femmes victimes de violence -- États-Unis -- Biographies; Divorce -- États-Unis -- Histoire -- 19e siècle.; Internement (Psychiatrie) -- États-Unis.; Femmes -- États-Unis -- Conditions sociales -- 19e siècle.; Femmes médecins.; Femmes victimes de violence; Femmes vivant avec un trouble de santé mentale; physicians; people with psychiatric illnesses; SOCIAL SCIENCE / General; Abused wives; Divorce; Mentally ill -- Commitment and detention; Physicians' spouses; Women physicians; Women -- Social conditions; United States; 1800-1899; Biographies; History